Managing Human Resources in the Latin American Context: The Case of Chile - Perez-Arrau, J (2012)
In this article several aspects of human resource management (HRM) in Chile will be examined. Initially Chile will be analysed in the context of Latin American culture and history, as it shares a number of common features with the rest of the countries of the region. Secondly, the arrival of HRM to Chile is explored, as well as how it is affected by the particular characteristics of the country. Thirdly, HRM research literature in the specific context of Chile is reviewed and analysed. Finally, some consequences are discussed, and it is concluded that Chile shares a unique history, culture, social particularities and problems with the other countries of the region, affecting the way in which HRM is deployed in organisations. It is also concluded that more research in this context is urgently needed. © 2012 Taylor and Francis Group, LLC.